An Integrated Landscape of Fear and Disgust: The Evolution of Avoidance Behaviors Amidst a Myriad of Natural Enemies - Doherty, Jean-François; Ruehle, Brandon (Frontiers in Ecology and Evolution, 2020)
Fear of natural enemies in non-human animals is a concept dating back to the time of Darwin. Now recognized as a nonconsumptive effect, the ecological and evolutionary impact of fear has been studied in a number of predator-prey systems within the last few decades. However, comparatively little consideration has been given to the nonconsumptive effects that parasites have on their hosts, which have evolved behaviors to avoid parasites, impacting habitat selection, mate choice, and foraging activity. These avoidance behaviors create a “landscape of disgust”, wherein hosts navigate to avoid parasites, akin to the “landscape of fear” in prey. Evolutionarily speaking, however, predators and parasites are but two examples of natural enemies. Pathogens, parasites, predators, and parasitoids, among others, each exert their own fitness cost on the victims they attack. Since animals likely evolve in the presence of multiple natural enemies, they must adopt a range of avoidance behaviors to navigate through the resulting “landscape of peril”. Therefore, in line with recent efforts to combine the landscapes of fear and disgust, we offer a theoretical framework to better understand the impacts of natural enemies on the evolution of trait-mediated avoidance behaviors in animals. More precisely, we look at how victims may evolve to allocate energy optimally among distinct avoidance behaviors under the selective pressures imposed by different types of natural enemy. This framework is then put into the more realistic context of a food web, which highlights the impact of trophic interactions and trophic level on the evolution of avoidance behaviors.